Oily-wastewater treatment using eco-friendly ceramic membranes derived from sugarcane bagasse waste: Optimization using response surface methodology - Nurhayati Jamalludin; Mohd Riduan Jamalludin; Siti Khadijah Hubadillah; Mohd Hafiz Dzarfan Othman; Mohd Azizi Hakim Jamalludin (Cleaner Chemical Engineering)
Treating oily-wastewater through separation technologies with advanced properties such as environmental-friendly and low cost is a challenging work. Herein, we successfully fabricated superhydrophic-superoleophilic green ceramic hollow fibre membrane prepared from sugarcane bagasse waste and modified through sol-gel method. Later, this study aims to optimize wastewater behaviour (pH, concentration and temperature) for oily-wastewater separation through green ceramic membrane using central composite design (CCD) of response surface methods (RSM). The three effective parameters analyzed were oil pH (3–11), oil concentration (10–10000 ppm), oil temperature (30–100 °C) and its combined effect to obtain high oil flux and excellent oil separation efficiency. Through the investigation it was found that the optimum value of pH, oil concentration and temperature were 10, 10.01 ppm and 69.04 °C. The result of the study has suggested that there are oil temperature has significantly influence the efficiency of the synthesized membrane separation performance. The fitted model was found to agree with the predicted and actual oil flux as well as separation efficiency which indicated by the high values of R2 = 0.954 and R2adj = 0.986. According to the optimized condition, the finding reported 4.71 % and 0.746 % average error for oil flux and separation efficiency which agrees with the forecasted and actual values. The novelty of this study lies in the development of an eco-friendly ceramic membrane derived from sugarcane bagasse waste, offering an innovative and sustainable solution for oily-wastewater treatment.